AWARENESS AND ATTITUDE OF PARENTS ABOUT FEMALE PARTICIPATION IN SPORTS - Soniha Aslam; Javed Shaikh (The Sky)
Aim: The present study spotlight on psychosocial factors that play vital role in influencing Participation and lack of participate of females in sports. The study discusses various difficulties of women’s participation in sports. Methodology: A self administered questionnaire was used as a tool to study. 200 subjects who were selected randomly for study purpose both government and private girls degree colleges Hyderabad. The filled questionnaire was collected and evaluated to examine the parent’s attitude towards girl’s participation in sports. Statistical analysis through Percentile and Frequency methods were done to find the parent’s attitude towards Female’s Participation in sports. The observations of the study shows that bulk of the parents acquire encouraging attitude towards female participation in sports. Despite this several psycho-cultural restraints hinders parents in showing the encouraging attitude.